The descending branch of the lateral circumflex femoral artery as an alternative conduit for coronary artery bypass grafting: Experience from an anatomical, radiological and histological study. Issue 6 (13th June 2016) - Loskot, Petr; Tonar, Zbynek; Baxa, Jan; Valenta, Jiri
Abstract : The descending branch of the lateral circumflex femoral artery (DBLCFA) has been suggested as an option for use in coronary artery bypass grafting (CABG). Our aim was to combine radiological examination, surgical and anatomical preparation, and histological assessment of the DBLCFA to map its variability and to assess the benefits of this conduit in cardiac surgery. The pelvic and femoral arteries were examined by CT angiography (CTA) in 100 patients (aged 68.3 ± 9.3 years) to assess the variability of the DBLCFA. Anatomical dissections were performed on 20 cadavers. In 15 patients, an autologous DBLCFA was implanted during CABG. In 35 samples, possible atherosclerotic lesions were examined histologically. The length of the potential DBLCFA conduits measured by CTA was 9.3 ± 2.9 cm, without correlating with the length of the thigh. Anatomical variations that would prevent the DBLCFA from being used in CABG were found in 27 out of 100 patients. Except for focal thickening of the intima, eccentric hypertrophy of the intima was found in three out of 35 samples. No inflammatory infiltration, foam cells, atheroma, or calcifications were found histologically. The DBLCFA is not to be used routinely or in preference to other grafts of choice. However, owing to its moderate variability, sufficient length, caliber, and rare atherosclerosis, it can be used in the absence of other suitable grafts as an alternative conduit implanted as a composite Y‐graft end‐to‐side to the internal thoracic artery in patients without diabetic angiopathy, neuropathy or peripheral artery disease who are undergoing extensive or repeat coronary revascularization. Clin. Anat. 29:779–788, 2016. © 2016 Wiley Periodicals, Inc.